A Review on Measures to Rejuvenate Immune System: Natural Mode of Protection Against Coronavirus Infection - Islam, Md. Aminul; Haque, Md. Atiqul; Rahman, Md. Arifur; Hossen, Foysal; Reza, Mahin; Barua, Abanti; Marzan, Abdullah Al; Das, Tuhin; Kumar Baral, Sumit; He, Cheng; Ahmed, Firoz; Bhattacharya, Prosun; et al. (Frontiers in Immunology, 2022)
SARS-CoV-2, a novel Corona virus strain, was first detected in Wuhan, China, in December 2019. As of December 16, 2021, almost 4,822,472 people had died and over 236,132,082 were infected with this lethal viral infection. It is believed that the human immune system is thought to play a critical role against the initial phase of infection when the viruses invade into the host cells. Although some effective vaccines have already been on the market, researchers and many bio-pharmaceuticals are still working hard to develop a fully functional vaccine or more effective therapeutic agent against the COVID-19. Other efforts, in addition to functional vaccines, can help strengthen the immune system in order to defeat the corona virus infection. Herein, we have reviewed some of those proven measures, following which a more efficient immune system can be better prepared to fight viral infection. Among these, dietary supplements like- fresh vegetables and fruits offer a plentiful of vitamins and antioxidants, enabling to build up a healthy immune system. While the pharmacologically active components of medicinal plants directly aid to fight against viral infection, supplementary supplements combined with a healthy diet will assist to regulate the immune system and will prevent viral infection. In addition, some personal habits, like- regular physical exercise, intermittent fasting, and adequate sleep, had also been proven to aid the immune system in becoming an efficient one. Maintaining each of these will strengthen the immune system, allowing innate immunity to become a more defensive and active antagonistic mechanism against corona-virus infection.From our knowledge,it is the first review including all possible suggestions for boost up immunity against Corona Virus. However, because dietary treatments take longer to produce beneficial effects in adaptive maturation, personalized nutrition cannot be expected to have an immediate impact on global outbreak. Keywords: COVID-19, Immune System, Healthy Diet, Fresh-vegetables and fruits, Vitamin and Antioxidants ,Medicinal plants, Metabolites, Physical exercise